Combined analysis of gut microbiota, diet and PNPLA3 polymorphism in biopsy‐proven non‐alcoholic fatty liver disease. (7th May 2021) - Lang, Sonja; Martin, Anna; Zhang, Xinlian; Farowski, Fedja; Wisplinghoff, Hilmar; J.G.T. Vehreschild, Maria; Krawczyk, Marcin; Nowag, Angela; Kretzschmar, Anne; Scholz, Claus; Kasper, Philipp; Roderburg, Christoph; et al.
Abstract: Background and aims: Non‐alcoholic fatty liver disease (NAFLD) is a global health burden. Risk factors for disease severity include older age, increased body mass index (BMI), diabetes, genetic variants, dietary factors and gut microbiota alterations. However, the interdependence of these factors and their individual impact on disease severity remain unknown. Methods: In this cross‐sectional study, we performed 16S gene sequencing using fecal samples, collected dietary intake, PNPLA3 gene variants and clinical and liver histology parameters in a well‐described cohort of 180 NAFLD patients. Principal component analyses were used for dimensionality reduction of dietary and microbiota data. Simple and multiple stepwise ordinal regression analyses were performed. Results: Complete data were available for 57 NAFLD patients. In the simple regression analysis, features associated with the metabolic syndrome had the highest importance regarding liver disease severity. In the multiple regression analysis, BMI was the most important factor associated with the fibrosis stage (OR per kg/m 2 : 1.23, 95% CI 1.10‐1.37, P < .001). The PNPLA3 risk allele had the strongest association with the histological grade of steatosis (OR 5.32, 95% CI 1.56‐18.11, P = .007), followed by specific dietary patterns. Low abundances of Faecalibacterium, Bacteroides and Prevotella and high abundances of Gemmiger were associated with the degree of inflammation, ballooning and stages of fibrosis, even after taking other cofactors into account. Conclusions: BMI had the strongest association with histological fibrosis, but PNPLA3 gene variants, gut bacterial features and dietary factors were all associated with different histology features, which underscore the multifactorial pathogenesis of NAFLD.